Громадська активність в Українській РСР у другій половині ХХ століття: форми протесту політичній системі - Малярчук, Олег; Malyarchuk, Oleg (My University, 2015)
У статті охарактеризовано форми активного й пасивного опору партійно-радянській політичній системі в Українській РСР у другій половині ХХ ст. Висвітлено тогочасний механізм реабілітації політв’язнів та повернення конфіскованого майна. Виокремлено зміни в тактиці: естафету боротьби перейняли дисиденти й розрізнені моло¬діжні націоналістичні організації. The article describes forms of active and passive resistance to the Soviet party-political system in the Ukrainian SSR in the second half of the twentieth century. Brezhnev era was characterized by contradiction and duality of processes which were taking place in the country. On the one hand, increasing the economic potential and growth of material welfare somewhat leveled totalitarian policies in all spheres of life. On the other - principles and freedoms declared in the highest state documents increasingly demonstrated their fictitious.
Public Activity in the Ukrainian SSR in the Second Half of the XXth Century: Political System Protest Forms
Keywords: УРСР; комуністична партія; ідеологія; дисиденти; націоналісти; репресії; the USSR; Communist Party; ideology; dissidents; nationalists; repressive crackdown; national memory